Correlation between Digital Literacy with Chemical Computational Ability: Chemistry Students at UIN Walisongo - Harahap, Lenni Khotimah; Drastisianti, Apriliana (LAVOISIER: Chemistry Education Journal, 2025)
This research aims to determine the relationship between digital literacy and chemical computing abilities of Chemistry Education students at UIN Walisongo Semarang. Digital literacy is an important competency that supports 21st century skills, including mastery of technology in chemistry learning. This research uses a quantitative approach with a correlational design. The research population was all 6th semester students taking the Computational Chemistry course, with a total sample of 56 students. The research instruments consisted of a digital literacy questionnaire, computational chemistry practice tests, observation sheets, and interviews. Data analysis was carried out using the Pearson correlation formula. The results showed that there was a positive and significant relationship between digital literacy and students' chemical computing abilities (r = 0.72; p 0.05). This means that students with high digital literacy tend to have better chemical computing skills. This research recommends strengthening digital literacy in the technology-based chemistry learning curriculum.